Validation in the agent-based modelling paradigm: problems and a solution. (17th October 2012) - Heath, B.L.; Ciarallo, F.W.; Hill, R.R.
This paper identifies problems in Agent-Based Modelling (ABM) validation and proposes a new modelling framework and diagramming technique to help solve those problems. The new framework relates the level of understanding of a real system with the appropriate model validation emphasis. The new diagramming technique, called the Conceptual Model for Simulation (CM4S) Diagram, is designed specifically for developing and documenting the conceptual model of a simulation while capturing appropriate validation criteria. An ABM simulation with real military implications is replicated in a proof of concept study. This paper advances ABM by identifying and helping to solve ABM validation challenges.